Assessing Adult Leisure Activities: An Extension of a Self-Report Activity Questionnaire - Jopp, Daniela (2010)
Everyday leisure activities in adulthood and old age have been investigated with respect to constructs such as successful aging, an engaged lifestyle, and prevention of age-related cognitive decline. They also relate to mental health and have clinical value as they can inform diagnosis and interventions. In the present study, we enhanced the content validity of the Victoria Longitudinal Study activity questionnaire by adding items on physical and social activities, and validated a shortened version of the questionnaire. Our proposed leisure activity model included 11 activity categories: three types of social activities (i.e., activities with close social partners, group-centered public activity, religious activities), physical, developmental, and experiential activities, crafts, game playing, TV watching, travel, and technology use. Confirmatory factor analyses validated the proposed factor structure in two independent samples. A higher-order model with a general activity factor fitted the activity factor correlations with relatively little loss of fit. Convergent and discriminant validity for the activity scales were supported by patterns of their correlations with education, health, depression, cognition, and personality. In sum, the scores derived from of the augmented VLS activity questionnaire demonstrate good reliability, and validity evidence supports their use as measure of leisure activities in young, middle-aged, and older individuals.